Knowledge Production, Mobilization and Standardization in Chile’S Hidroaysén Case - Broitman-Rojas, C (Springer Netherlands, 2018)
The Aysén Hydroelectric Project in Chilean Patagonia proposed the construction of the country’s largest power facility to supply its capital, nearly 2,000 kilometres away. We seek to explain the way science, politics, law, business and the civilian population are joined up. To this end, we analyse the project’s evolution, the construction of techno-scientific arguments by the participants and how Chilean regulations are adapting to this process. © 2017, Springer Science+Business Media B.V.